Pair Programming and the Level of Knowledge in the Formation of Pairs - Sobral, Sónia Rolland (2021)
The pandemic situation COVID-19 requires teachers to rethink some of the activities proposed to students since even though they are physically in the same room at the university, they cannot join and must maintain a social distance. The curricular unit of introduction to programming in the first year of computer courses requires several activities: students only learn by doing. One of the activities that has been used a lot in the academic community is pair programming: a single computer for two students working together. In the case that this article reports the pair works sharing a ZOOM room and alternates the position of driver (writes the code) with navigator (one that comments on the code). This article uses the technique of pair programming for writing top-down, algorithm and traces to verify the behavior of variables along the algorithm. If the pair programming technique has had very interesting results in terms of task speed and code quality far superior to programmers alone, there are some doubts about the problem of the constitution pf the groups. In this article we use two opposite strategies: group students with opposite knowledge or group students with similar knowledge. We found that students who prefer this activity are the worst ones (in both strategies) and the best students when grouped with colleagues with similar knowledge.